More than just a KRAS inhibitor: DCAI abrogates the self-renewal of pancreatic cancer stem cells in vitro - Yuan, Han Teh; Rui, Jing; Ramasamy, Rajesh; Kok, Lian Ho; Sagineedu, Sreenivasa Rao; Stanslas, Johnson (Tech Science Press, 2023)
Growing evidence indicates that pancreatic cancer stem cells (CSCs) contribute to cancer recurrence via chemoresistance, and their growth is sustained by self-renewal. Targeting the self-renewal of pancreatic CSCs is a crucial strategy to eradicate them. Here, we are the first to describe a known KRAS inhibitor, 4,6-dichloro-2-methyl-3-aminoethyl-indole (DCAI), as a novel anti-pancreatic CSC agent that abrogates the self-renewal of pancreatic CSCs. Cell viability assay was used to determine the cytotoxicity of KRAS binders in pancreatic cancer cell lines with either wild-type KRAS (BxPC-3) or clinically relevant KRAS mutations (PANC-1, Capan-2, and MIA PaCa-2). The tumoursphere assay was utilised to investigate the effect of DCAI on the self-renewal of pancreatic CSCs, and its mechanism of action was examined by Western blotting. The growth of pancreatic cancer cells remains unaffected by the binding of Benzimidazole (BZIM) to both wild-type and oncogenic KRAS. DCAI and Kobe0065 were equally potent in pancreatic cancer cell lines, except for Capan-2, in which DCAI (GI50=25.8 ± 0.8 μM) was more potent than Kobe0065 (GI50=54.0 ± 1.0 μM). Capan-2 tumourspheres were markedly irresponsive to gemcitabine (IC50>100 μM), while DCAI abrogated the formation of Capan-2 tumourspheres profoundly (IC50=30 μM). Upon treatment with DCAI, CRAF, ERK1, ERK2, and AKT activations were significantly inhibited, and SOX2 expression was greatly reduced in Capan-2 tumourspheres. Our present study revealed that DCAI depletes pancreatic CSCs by inhibiting self-renewal via KRAS-CRAF-ERK1/2-SOX2 and KRAS-AKT-SOX2 axes. Our findings suggested that KRAS is a valid therapeutic target in pancreatic CSCs for eradicating cancer recurrence.